(untitled) (Research, Society and Development, 2022)
This work aimed to socialize the experience lived by a nursing student in an extension project focused on the health of the elderly. This academic extension is one of the pillars for university education, it has a sense of extreme importance in the process of social interaction with the community, especially for planning and executing health promotion and prevention actions. The students’ relationship with extension projects has made them aware of the reality that surrounds them and how they need to be participatory. A descriptive study of the experience report type (RE) was designed, which according to the literature. The extension project that resulted in the writing of this report took place from February to December 2019 in the auditorium of a Higher Education Institution. This project was conceived by a group of nursing students, with a view to comprehensive health care for the elderly from the perspective of the Unified Health System (SUS). This project took place in three moments, reception, health education and finally spirituality. The present experience allowed the immersion of students in the health of the elderly, being able to work well on the quality of life and explore health education in different ways. In this way, it is expected that the practices experienced in this project will provide a differential in the training of students, enriching the quality of future health professionals and strengthening qualified assistance.